2021
DOI: 10.1371/journal.pone.0255427
|View full text |Cite
|
Sign up to set email alerts
|

6-month mortality and readmissions of hospitalized COVID-19 patients: A nationwide cohort study of 8,679 patients in Germany

Abstract: Background COVID-19 frequently necessitates in-patient treatment and in-patient mortality is high. Less is known about the long-term outcomes in terms of mortality and readmissions following in-patient treatment. Aim The aim of this paper is to provide a detailed account of hospitalized COVID-19 patients up to 180 days after their initial hospital admission. Methods An observational study with claims data from the German Local Health Care Funds of adult patients hospitalized in Germany between February 1 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
2
17

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 27 publications
5
61
2
17
Order By: Relevance
“…While the severe and critical represented 21% of COVID-19 patients, the in-hospital infection fatality rates vary from 11% to 31% [ 8 , 9 , 10 ]. Three and six months all-cause mortality in patients hospitalized with COVID-19 was estimated at 28% and 30%, respectively [ 11 ]. However, the overall mortality rate in the population is lower ranging 0.3–5% [ 8 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the severe and critical represented 21% of COVID-19 patients, the in-hospital infection fatality rates vary from 11% to 31% [ 8 , 9 , 10 ]. Three and six months all-cause mortality in patients hospitalized with COVID-19 was estimated at 28% and 30%, respectively [ 11 ]. However, the overall mortality rate in the population is lower ranging 0.3–5% [ 8 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…We must ensure the follow up of these patients, with a view to finding out how long these symptoms persist and whether they develop into chronic disorders. These conditions can lead to hospital readmission, estimated at around 3.6-4.5% in the first 30 days ( 24 , 25 ) and up to 27% after six months ( 26 ), resulting in a dramatic impact on communities and healthcare systems.…”
mentioning
confidence: 99%
“…9%, with the predictors of coagulopathy, age, and obese type II that were correlated with 180 days mortality after ICU discharge (18). in Australia, similar results demonstrated that ICU length of stay was correlated with long-term mortality but, comorbidities, age, Acute physiology score predict the long-term mortality better than the length of stay (19).…”
mentioning
confidence: 67%